2018
DOI: 10.1074/jbc.ra117.000100
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate kinase M2 interacts with nuclear sterol regulatory element–binding protein 1a and thereby activates lipogenesis and cell proliferation in hepatocellular carcinoma

Abstract: Dysregulation of lipid metabolism is common in cancer cells, but the underlying mechanisms are poorly understood. Sterol regulatory elementbinding proteins (SREBPs) stimulate lipid biosynthesis through transcriptional activation of lipogenic enzymes. However, SREBPs' roles and potential interacting partners in cancer cells are not fully defined. Using a biochemical approach, we found here that pyruvate kinase M2 (PKM2) physically interacts with the nuclear form of SREBP-1a (nBP1a), by binding to amino acids 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…The previous study reported that PKM2 interacts with nuclear sterol regulatory element-binding protein 1a and thereby activates lipogenesis and cell proliferation in hepatocellular carcinoma (Zhao et al, 2018). Sterol regulatory element-binding protein-1a (SREBP-1a), SREBP-1c, and SREBP-2 are members of the SREBP family of transcription factors.…”
mentioning
confidence: 99%
“…The previous study reported that PKM2 interacts with nuclear sterol regulatory element-binding protein 1a and thereby activates lipogenesis and cell proliferation in hepatocellular carcinoma (Zhao et al, 2018). Sterol regulatory element-binding protein-1a (SREBP-1a), SREBP-1c, and SREBP-2 are members of the SREBP family of transcription factors.…”
mentioning
confidence: 99%
“…Zhao et al (9) further show that PKM2-nBP1a complex formation results in increased nBP1a stability and Thr-59 phosphorylation. By using an nBP1a mutant (T59A) lacking the ability to be phosphorylated, they demonstrated the importance and fundamental nature of nBP1a Thr-59 phosphorylation by recapitulating these results in lung, colorectal, and breast cancer cell lines.…”
mentioning
confidence: 95%
“…Thus, Zhao et al (9) have clearly shown that PKM2-nBP1a complex formation and subsequent Thr-59 phosphorylation stimulates nBP1a-dependent transcription and lipid accumulation, which are critical events necessary for cell proliferation and tumorigenesis (Fig. 1).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Lipids not only function as second messengers to transduce signals within cells but also serve as important energy sources when nutrients are limited [3]. Accumulating experiments have demonstrated that lipid metabolism is substantially reprogrammed in cancers [4][5][6]. e obvious feature of lipid metabolism in cancers is an increased rate of lipogenesis and mitochondrial fatty acid β-oxidation.…”
Section: Introductionmentioning
confidence: 99%